An Engineered IgG–VHH Bispecific Antibody against SARS‐CoV‐2 and Its Variants (Small Methods 12/2022). Issue 12 (13th December 2022) - Chi, Hang; Wang, Lei; Liu, Chanjuan; Cheng, Xiaohe; Zheng, Hailiang; Lv, Lilang; Tan, Yongcong; Zhang, Nana; Zhao, Suoqun; Wu, Mei; Luo, Dan; Qiu, Hongying; et al.
Abstract : Front Cover In article number 2200932, Lang, Shao, Deng, Wang, Qin, and co‐workers designed and developed a novel bispecific antibody (bsAb), which combines the strengths of IgG and nanobody, and comprehensively characterized its potency to block SARS‐CoV‐2 and its variants in vitro and in vivo. This universal bsAb platform provides an effective and promising tool for the development of therapeutics against COVID‐19 as well as other diseases.